Collecting streaming music increases listening enjoyment - Bergman, Ofer; Gradovitch, Noa (Personal and ubiquitous computing, 2023)
Streaming music application users can collect music (e.g., by “liking” songs or adding them to playlists) at no additional cost. However, most people reduced their collection size drastically when moving to streaming technology. The aim of the current study was to determine whether increasing streaming collection size would cause an increase in listening enjoyment. We conducted a within-subject controlled experiment where we asked our 40 participants, who have small collections, to rate their listening enjoyment in three different conditions: baseline condition — regular listening without manipulation, experimental condition — where they were asked to collect music and listen to it, and platform condition — where they were asked to listen to the songs suggested to them by their application algorithm. Listening enjoyment was rated in real time to avoid memory bias. Results indicate that (a) the participants’ current listening enjoyment was lower than they estimated it was, and seems in need of improvement; (b) collecting songs was more pleasurable than difficult; and (c) listening to collected songs significantly increases listening enjoyment and reduces enjoyment dropdowns over both baseline and platform condition. These results strongly suggest that streaming music providers should encourage their users to collect music. In our discussion, we shed light on a fundamental design problem that most streaming applications have which might discourage music collecting, and suggest designs aimed to encourage collecting.